Analisis Kesempurnaan Akhlak Nabi Muhammad Saw Ditinjau Dari Al Qur’an dan Sunnah - Raju Pratama Marronis; Ibnu Majah Arifin; Elsya Frilia Ananda N; Wismanto Wismanto; Dini Gita Sartika (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
All of the behavior of the Prophet Muhammad reflects Islam. By knowing the Prophet Muhammad SAW from a social perspective, social values ​​can emerge in Islam. This study is expected to increase enthusiasm for emulating the Islamic morals of the Prophet Muhammad SAW which are considered so difficult that they are still considered low even among the faithful. Islam itself.Library research uses a qualitative approach. The emphasis is placed on qualitative research using various methods, including interpretive and naturalistic approaches to the research subject. This research examines the Prophet Muhammad as mentioned in the book 'Islam' by Fazlur Rahman. The results of this research are an investigation into the form of secular Islamic morality of the Prophet Muhammad SAW. It is recorded that the Prophet never put his personal interests first. On the other hand, the holy form of Islamic morals of the Prophet Muhammad SAW originates from the main postulates of Islam, namely the Al-Qur'an and Hadith. This research reveals that the Al-Qur'an and Hadith provide an explanation of all the Islamic morals of the Prophet Muhammad SAW. This is in line with Aisyah's statement that the Prophet's morals are Al -Quran.